Perancangan Sistem Pintu Otomatis Berbasis Arduino Menggunakan Bluetooth Di Cv.Aabc Software Karawang - Kurnia, Okto; Rahmadiani, Ulfa Siti (Journal of Information and Technology, 2024)
Technological advances require humans to further increase effectiveness and efficiency in various things. Therefore, humans are expected to be able to carry out activities efficiently in a relatively short time. The door is a medium used as a way to enter or exit. So an automatic door system design is needed so that it can be controlled remotely. The purpose of this study is to create a prototype of an Arduino-based automatic door. This automatic door is designed using the HC-05 Bluetooth Module, Arduino Uno microcontroller, LCD, I2C, LED and Servo motor. And also using the Waterfall method, the microcontroller receives input from the HC-05 Bluetooth, then the microcontroller provides output to the I2C and LCD by entering the Password on the Boarduino Application via an Android Smartphone. Furthermore, the output from the LCD and LED goes to the Servo motor which functions to open and close the door if the Password is correct. And also using the prototype method and the results of this automatic door prototype can provide convenience for opening and closing the door so that it can save time and energy.